Introduction to RF and microwave passive components - Wallace, Richard (Telecommunication engineer); Andreasson, Krister (Artech House microwave library, 2015)
This authoritative new resource provides an overview and introduction to working with RF, microwave, and high frequency components. From transmission lines, antennas, millimeter waves, ferrites, hybrids, power dividers and filters, this book focuses on practical, time-to-market issues to help with projects in the field